The Impact of Social Media Marketing and Brand Engagement on Marketing Performance of Fashion MSMEs in Pontianak with Online Marketing Effectiveness as a Mediating Variable - Veny Stevany; Stivenes Tjin Siam (Economic: Journal Economic and Business, 2025)
Advances in digital technology have encouraged MSMEs, particularly in the fashion industry, to utilize social media as a primary marketing tool. This study aims to examine the influence of social media marketing and brand engagement on marketing performance, with online marketing effectiveness as a mediating variable. This study was conducted using a quantitative approach using a sample of 125 fashion MSMEs in Pontianak selected through purposive sampling. The data were analyzed using Structural Equation Modeling (SEM) with the help of AMOS 29.0. Based on the analysis, it was found that social media marketing significantly influences marketing performance and digital marketing effectiveness. Brand engagement has been shown to increase online marketing effectiveness, but does not show a direct impact on marketing performance. Furthermore, marketing effectiveness was unable to mediate the relationship between the two independent variables and marketing performance. The results of this study indicate that social media still plays an important role in driving the marketing performance of fashion MSMEs, while brand engagement and online marketing effectiveness need to be improved to make a real contribution to increasing sales and customer loyalty.